2000
DOI: 10.1063/1.373779
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence emission pattern of organic light-emitting diodes: Implications for device efficiency calculations

Abstract: The electroluminescence (EL) pattern emitted through the surface and edge of the glass substrate of two efficient polymer light-emitting diodes (LEDs) has been characterized. The surface emission is nearly Lambertian, while the edge emission comprises discrete substrate reflection and leaky waveguide modes. A simple “half-space” optical model that accounts for optical interference effects of the metal cathode–reflector is developed to extract the location and orientation of the emitting dipoles from these patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
148
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(151 citation statements)
references
References 42 publications
1
148
0
2
Order By: Relevance
“…4 To explore the nature of the SNEE, we begin by noting that the optical propagation loss in a metal-clad waveguide is primarily caused by the strong absorption, estimated at ϳ10 3 cm −1 of the evanescent tail of the optical field that penetrates the metal electrode. 4,9 The ITO is also lossy, 10 particularly at Ͻ450 nm. Hence, the waveguided light would be completely absorbed before it contributes to any far-field edge emission ͑see below͒.…”
Section: Spectrally Narrowed Edge Emission From Organic Light-emittinmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To explore the nature of the SNEE, we begin by noting that the optical propagation loss in a metal-clad waveguide is primarily caused by the strong absorption, estimated at ϳ10 3 cm −1 of the evanescent tail of the optical field that penetrates the metal electrode. 4,9 The ITO is also lossy, 10 particularly at Ͻ450 nm. Hence, the waveguided light would be completely absorbed before it contributes to any far-field edge emission ͑see below͒.…”
Section: Spectrally Narrowed Edge Emission From Organic Light-emittinmentioning
confidence: 99%
“…Losses occurred at each reflection; they were larger for TM modes, and upon propagation in the ITO when a complex refractive index n = 1.90− 0.04i was introduced. 10 However, these losses did not preclude propagation distances d ϳ 100 m without optical gain. Yet for d ജ 1 mm, some gain was required.…”
Section: Spectrally Narrowed Edge Emission From Organic Light-emittinmentioning
confidence: 99%
“…The simulations of the charge transport and charge distribution in organic light emitting devices have been reported [3][4]. There have been several works on calculating the emission pattern [5] and external coupling in OLEDs [6]. It has been shown that the emission from an OLED can be varied through interference effects by changing the thickness of the organic layer in an OLED with a dielectric layer located below the ITO anode [7] or by changing the thickness of a ZnSe layer on top of the metal cathode [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…External quantum efficiencies (EQEs) of 30% have been reported recently [1][2][3][4][5][6] ; this is considered to be the light-outcoupling efficiency limit of phosphorescent OLEDs under isotropically oriented transition dipole moments 4 . It has long been recognized that orienting the transition dipole moment of an emitter along the horizontal direction (parallel to the substrate) can enhance the outcoupling efficiency beyond that achieved under isotropic orientation, as demonstrated in polymer-based and vacuumevaporated fluorescent molecule-based OLEDs [7][8][9][10][11][12][13] . Nonetheless, the orientation of the transition dipole moments of iridium complexes used as phosphorescent emitters in efficient OLEDs is typically considered to be isotropic because they are near-globular and small enough to have configurational diversity in their orientational states.…”
mentioning
confidence: 99%